(untitled) (Entrepreneurship Journal for Finance and Business, 2024)
Social media platforms are distinguished by their ease of access to different categories of audiences and the high interactivity they provide, making them an effective means for companies and product owners to enhance their brands and communicate with the public directly and effectively. Since using celebrities on these platforms is considered one of the principles of influencer marketing, the advertisements they make have high credibility with consumers, which makes them an effective way of marketing for companies. The study aimed to identify the rates of Iraqi consumers’ use of celebrities’ pages on social media platforms, and the most important conditions for the credibility of advertising on celebrities’ pages from the consumer’s perspective. This study belongs to quantitative descriptive studies that aim to know the effect of the credibility of celebrities’ advertisements on social media platforms on purchasing intentions among consumers. The researcher relied on the electronic questionnaire (Web questionnaire) as a tool for collecting data, while the researcher chose a deliberate sample of about (400) Iraqi consumers from rural and urban areas who follow the pages of celebrities on social media platforms. The study found the following: The motives for using celebrity pages on social media came in first place, and this indicates the respondents’ interest in following celebrity pages. Expressing “like” came at the top of the ways the respondents of the study sample interacted with celebrity advertisements, followed by expressing “unlike” and “comments,” as the most common interaction pattern on these sites is “like,” “dislike,” and “comment.” “Photos with Text” came in first place in terms of posts that the respondents interacted with, followed by “recorded videos of influencers using the product,” then “Status/Text Posts only.” The phrases that explain the dimensions of credibility (trust - attractiveness - experience) of the celebrity came in first place, and this indicates the availability of the dimensions of credibility among celebrities (experience, trust, and attractiveness) from the point of view of the respondents.